2010
DOI: 10.1186/1471-2229-10-278
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting EST databases for the development and characterization of EST-SSR markers in castor bean (Ricinus communisL.)

Abstract: BackgroundThe castor bean (Ricinus communis L.), a monotypic species in the spurge family (Euphorbiaceae, 2n = 20), is an important non-edible oilseed crop widely cultivated in tropical, sub-tropical and temperate countries for its high economic value. Because of the high level of ricinoleic acid (over 85%) in its seed oil, the castor bean seed derivatives are often used in aviation oil, lubricants, nylon, dyes, inks, soaps, adhesive and biodiesel. Due to lack of efficient molecular markers, little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
99
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 39 publications
(63 reference statements)
36
99
3
3
Order By: Relevance
“…The proportion of polymorphic primers was 41.1 % when null allele primers and those that harbor introns were excluded resulting in 2.97 alleles per marker. This revealed that the polymorphic ratio of EST-SSR primers to be at medium level in castor (Qiu et al 2010). PIC values for the tested primers varied from a low of 0.27 (Rc DES 596) to a high of 0.49 (Rc DES 592) with an average value of 0.332.…”
Section: Polymorphism Of Est-ssrsmentioning
confidence: 88%
See 4 more Smart Citations
“…The proportion of polymorphic primers was 41.1 % when null allele primers and those that harbor introns were excluded resulting in 2.97 alleles per marker. This revealed that the polymorphic ratio of EST-SSR primers to be at medium level in castor (Qiu et al 2010). PIC values for the tested primers varied from a low of 0.27 (Rc DES 596) to a high of 0.49 (Rc DES 592) with an average value of 0.332.…”
Section: Polymorphism Of Est-ssrsmentioning
confidence: 88%
“…Fig. 1 Total number of amino acid distribution, total repeats and number of loci identified whereas Qiu et al (2010) reported 96.9 %. Hence, from both the studies it can be concluded that in castor genome MNR, A/T are the richest repeat.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 3 more Smart Citations